Наративна психологія та легітимація українського «історіографічного метанаративу» - Ващенко, В. (Інститут історії України НАН України, 2008)
In the article are researched the problems of legitimation and construction of Ukrainian historiographical metanarrative in the spatium of theoretical constructions of narrative psychology ( J. Bruner’s con ception) and therapeutic prospects of post -rationalistic cognitive psychology (V. Guidano’s theory of identity) These new approaches have allowed to compencate the negative results of post-modern destruction of historical metanarative.